Faktor-Faktor yang Mempengaruhi Depresi pada Lansia Pensiunan di Kecamatan Jekan Raya Kota Palangka Raya: Factors Affecting Depression in Retired Elders in Jekan Raya Subdistrict, Palangka Raya City - Syam’ani, Syam’ani (Jurnal Surya Medika (JSM), 2019)
The population of the population in the world is increasing day by day. One of the age groups that have a significant increase in the elderly group. Projections and data found about the elderly are a concern that is of interest to the whole world because along with the increase in population it is accompanied by physical and psychological problems that accompany it. This study aims to identify factors that affect depression in retired elderly people. The design used in this study uses a research design: "CROSS-SECTIONAL". In this study, the population is elderly retirees who live in the area of Jekan Raya Subdistrict, Palangka Raya City. The sampling technique in this study uses consecutive sampling technique, which is the best type of non-probability sampling, that is, all objects that come sequentially and meet the selection criteria are included in the study until the number of subjects needed is fulfilled, namely as many as 100 people. The results showed that there was no significant relationship between sex (p: 0.671), employment status (p: 0.994), marital status (p: 0.726), education (p: 0.988), and the level of depression in retired civil servants in Jekan Subdistrict Raya Kota Palangka Raya. This research is expected to contribute positively to the management of elderly people with depression so that they are able to adapt to changes that occur due to the aging process.